Acute and developmental toxic effects of mono-halogenated and halomethyl naphthalenes on zebrafish (Danio rerio) embryos: Cardiac malformation after 2-bromomethyl naphthalene exposure. (15th March 2022) - Park, Jungeun; Kim, Yurim; Jeon, Hwang-Ju; Kim, Kyeongnam; Kim, Chaeeun; Lee, Seungki; Son, Jino; Lee, Sung-Eun
Abstract: Polyhalogenated polycyclic aromatic hydrocarbons (HPAHs) represent a major environmental concern due to their persistency and toxicity. Among them, mono-halogenated (HNs) and halomethyl naphthalenes (HMNs) are not well-studied, and the toxicity of many HNs to fishes has not been reported. In this study, we exposed zebrafish ( Danio rerio ) embryos to naphthalene and five HNs at concentrations ranging from 0.25 to 2.0 mg L −1 to assess acute toxicities and developmental effects. Among them, 2-bromomethyl naphthalene (2-BMN) produced moderate lethal effects (96-h LC50 = 1.4 mg L −1 ) and significantly reduced hatchability. Abnormal phenotypes, including pericardial edema, spine curvature, and shortened body length, were also induced by 2-BMN (96-h EC50 = 0.45 mg L −1 ). Treatments of 0.5–2.0 mg L −1 2-BMN evoked cardiac malformations via significant down-regulation of the cacna1c gene, which codes the voltage-dependent calcium channel, at 72 hpf and up-regulation of the nppa gene, responsible for the expression of natriuretic peptides, at 96 hpf in zebrafish. One presumable toxic photo-dissociated metabolite of 2-BMN, the 2-naphthylmethyl radical, may be responsible for the toxic effect on zebrafish embryos. HPAHs must be monitored and managed due to their adverse effects on living organisms at low concentrations. Graphical abstract: Image 1 Highlights: 2-Bromomethyl naphthalene (2-BMN) showed potent lethal effects to zebrafish embryos. 2-BMN caused malformations in zebrafish embryos such as pericardial edemas. 2-BMN induced abnormal heart formation in Tg(cmlc2:EGFP) with lower heart beat rate. An arrythmia-related nppa gene during development was upregulated by 2-BMN treatment.